2012
DOI: 10.1002/jemt.22117
|View full text |Cite
|
Sign up to set email alerts
|

Genistein affects ovarian folliculogenesis: A stereological study

Abstract: The effects of short-term genistein exposure on ovarian folliculogenesis in immature rats were examined stereologically. To determine whether genistein acts as an estrogen agonist or antagonist, the results were compared with the effects of 17α-ethynylestradiol. Immature female rats received 50 mg/kg/bw of genistein in dimethyl sulfoxide subcutaneously daily for three consecutive days from 18 to 20 days. The second group was injected with 1 μg/kg/bw of 17α-ethynylestradiol in olive oil in the same schedule. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Glycine max is rich in phytoestrogens, however the types and amounts of phytoestrogens change according to the extraction method and the solvent used forthe extaction (Anthony et al 1996, Delclos et al 2001, Medigovic et al 2012. Luthria and Natarajan (2009) used seven different solvent mixture and various extraction methods for the extraction of isoflavons from soy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycine max is rich in phytoestrogens, however the types and amounts of phytoestrogens change according to the extraction method and the solvent used forthe extaction (Anthony et al 1996, Delclos et al 2001, Medigovic et al 2012. Luthria and Natarajan (2009) used seven different solvent mixture and various extraction methods for the extraction of isoflavons from soy.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study byMedigovicet al (2012), genistein decreased primordial, primary, secondary follicle count but increased atretic follicle count, revealing its estrogen antagonist effect. On the other hand, estrogen agonist effect of genistein was also demonstrated by its capacity to enhance the number of the follicles which develop from preantral phase to antral phase (Medigovic et al 2012). In another study, the toxicity of genistein was investigated and it was reported that there was no significant difference in the primordial follicle number (Lamartiniere et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Every 10th section from each of the tissue blocks was analyzed as previously described [17]. Follicular parenchyma included follicles in different stages of folliculogenesis, whereas ovarian stroma contained interstitial glands, blood vessels, and ovary connective tissue.…”
Section: Stereological Estimation Of Ovary Volumementioning
confidence: 99%
“…Namely, in vivo studies have demonstrated that genistein alters the development of a female reproductive system, including delaying of estrous cycles and induction of subfertility and infertility [15]. In addition, we have previously reported that genistein had an inhibitory effect on the initial phase of folliculogenesis and, at the same time, stimulated the pituitary gonadotropic cells in immature, estrogen-deprived animals [16,17]. Still, whether the phytoestrogens would exert their effects on the pituitaryovarian axis in a similar estrogen low hormonal milieu of middle-aged rats, fraught with other physiological challenges, remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Design-based stereology is considered the gold standard for estimating the total number of cells [Manojlović-Stojanoski et al, 2010;Ristić et al, 2014] or morphological structure in organs, such as follicles in the ovary [Myers et al, 2004;Charlston et al, 2007;Ristić et al, 2008;Medigović et al, 2012] or nephrons in the kidney [Cullen-McEwan et al, 2012]. Estimation of the total number of gonadotrophic cells in the pituitary gland in combination with another histochemical/stereological and biochemical technique may provide evidence whether the prenatal exposure to Dx induces developmental programming of the hypothalamo-pituitary-gonadal axis at the pituitary level in the neonatal, infant and peripubertal female offspring.…”
Section: Effects Of Prenatal Dexamethasone On the Rat Pituitary Glandmentioning
confidence: 99%